Optimalisasi Media Digital Sebagai Sarana Penyampaian Informasi di Tengah Pandemi Covid-19 - Sekar Fitria Sari; Yulia Puspita (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This community service was carried out as a realization of the students thematic community service program (KKN) for the prevention and management of the impact of Covid-19. The community service program which was held by Universitas Pendidikan Indonesian has the theme of the community service on prevention and management of the impact of Covid-19 in the education and economy sector during the new normal adaptation period. This program is conducted for 30 days from 17 November to 17 December 2020 at Menes district Pandeglang, Banten. This program tried to solve some community problems in several aspects. The first activities carried out during this community service program was in the field of education, such as enhancing learning courageously, mentoring students parents and assisting with school administration. The second activity was focused on preventing Covid-19 spread for school and the children community. This activity was carried out in online using information technology such as via YouTube, Google, and other social media. This optimizing digital media result a better in achieving the goals of increasing community awareness on preventing Covid-19 spreads.